(untitled) (Calidad, Tecnología y Desarrollo Agroindustrial, 2018)
The coffee chaff is a residue generated during processing of grain coffee, its accumulation cause contamination problems in soil and air. However, due to its lignocellulosic nature, it has a high energy potential, which makes it a by-product of added value in this sector, as it is transformed into combustible briquettes or ecological firewood. In this sense, this work developed a artisanal technological proposal to valorize this waste, through its chemical characterization, the identification of the process for its conversion to a potential fuel. The chaff was transformed, at two scales: at the laboratory level and at the pilot plant level in a community of the coffee sector through the operations of grinding, sifting, selection and addition of binder, pressing and drying. The briquettes produced were evaluated with respect to firewood, obtaining an improvement in terms of ignition time, combustion time, and percentage of waste. It’s reflects, a potential area of entrepreneurship for the coffee sector.